«Арештувати як українського есера...» (до біографії професора філософії та педагогіки Одеського державного університету Михайла Гордієвського) - Левченко, В.; Петровський, Е. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2008)
Based on the unknown documents of former Soviet security services, the authors reconstructed the milestones of political and scientific activity of Mykhailo Hordievskyi, a professor of philosophy and pedagogic of Odessa State University.